CompTIA Linux+ Portable Command Guide : All the commands for the CompTIA XK0-004 exam in one compact, portable resource, 2nd Edition - Rothwell, William (Pearson IT Certification, 2019)
For each exam objective, the key commands and configuration files will be detailed. The CompTIA Linux+ Portable Command Guide provides a single point of reference while studying for the certification exams as well as a valuable resource after the candidate has successfully passed the exams. The guide summarizes all commands, keywords, command arguments, and associated prompts. Configuration examples are provided throughout the book to give a better understanding of how these commands are used. This guide is not meant to replace any existing learning materials but rather serve as a supplementary guide to assist readers in the proper use of the many different commands to use on a regular basis and that are required to successfully pass the exams.